Mikrobiota–Usus–Otak sebagai Jaringan Metabolik dan Pengatur Kontrol Energi - Raymond R. Tjandrawinata (PT Dexa Medica, 2025)
This article examines the gut–brain axis in the pathophysiology of type 2 diabetes as a complex communication network that shapes glucose metabolism, systemic inflammation, gut hormone function, and eating behavior. By integratingevidence from metagenomic, neuroendocrine signaling, and modern pharmacotherapy studies, the article argues that type 2 diabetes is not merely a glycemic disorder, but also an internal ecological disruption involving microbiota interactions, theenteric nervous system, the vagus nerve, and metabolic regulatory centers in the brain. This perspective also highlights the clinical implications of emerging therapeutic agents such as GLP-1 agonists and dual GIP/GLP-1 agonists. This articleconceptualizes type 2 diabetes as an interorgan communication disorder that can be ameliorated through multilevel interventions including microbiota modulation, restoration of incretin, and precision nutrition strategies.